REENVISIONING ARTISTIC CREATIVITY: MODERN / POSTMODERN IMPLICATIONS OF BALZAC’S “THE UNKNOWN MASTERPIECE” - JUDOVITZ, Dalia (Studia Universitatis Babeș-Bolyai Philosophia, 2020)
This study explores Honoré de Balzac’s iconic representation of artistic creativity in The Unknown Masterpiece by focusing on an unexamined aspect of his text, namely the seminal role played by critical reception and consumption in artistic production. This influential tale is examined in terms of its artistic and philosophical contributions to reenvisioning creativity by modern and postmodern critics and thinkers. Challenging the ideology of the artist as creative genius, this analysis targets the processes, labor and materials of artistic production and its relations to critical consumption. At issue is the expressive potential of the art work in its creative capacities to bring about the new, to happen and make things happen.